2020
DOI: 10.1136/bmjopen-2019-034967
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement: loneliness in older adults, the 21st century social determinant of health?

Abstract: ObjectiveThe purpose of this consensus statement is to determine the state of the field of loneliness among older people, highlighting key issues for researchers, policymakers and those designing services and interventions.MethodsIn December 2018, an international meeting on loneliness was held in Belfast with leaders from across the USA and Europe. A summary of the conclusions reached at this event is presented following a consensus-building exercise conducted both during this event after each presentation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 28 publications
3
77
0
5
Order By: Relevance
“…In addition to the selection of a standardized assessment tool however, training and referral pathways will also be required to facilitate a useful response. Unfortunately, the evidence to date on effective interventions for loneliness remains greatly limited with further high-quality studies involving large samples and diverse populations needed ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the selection of a standardized assessment tool however, training and referral pathways will also be required to facilitate a useful response. Unfortunately, the evidence to date on effective interventions for loneliness remains greatly limited with further high-quality studies involving large samples and diverse populations needed ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the approaches used to address loneliness, at least in a UK context, are provided and funded by non-governmental organisations, often on shoestring budgets, meaning that any evaluations undertaken tend to be minimal in scope. A recent consensus statement from a group of leading international researchers working in the field of gerontology and loneliness also concluded that the current evidence base is dominated by "low-quality trials, small samples, a lack of theoretical frameworks or understanding of loneliness, diverse or undefined target groups, mixed measures of loneliness and short follow-up periods to assess longer term impact" [50]. Limits in the robustness of this evidence-base on what works may make it more difficult for both health service budget holders and local government authorities, who are responsible for public health in England, to determine how to combat loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in the 1980s, it was recognized that the lack of meaningful social relationships (or lack of meaningful relatedness) is a social determinant of poor health outcomes, associated with an increased risk of death from a variety of causes [5]. It is now more widely accepted that poor social support and loneliness can adversely affect physical, emotional, and mental well-being [6][7][8], is linked to an increased premature mortality risk [9,10] and correlates to adverse health outcomes such as depression, psychosocial maladjustment, poor coping behavior, low health promotion behavior, compromised well-being, reduced quality of life, and self-actualization [11]. Loneliness, specifically, has been called "the 21 st century social determinant" of poor outcomes in health.…”
Section: Introductionmentioning
confidence: 99%